A low profile aperture coupled antenna with broadband circular polarization characteristics for UHF RFID applications. Issue 6 (31st December 2018) - Xing, Zijian; Chen, Bo‐Yu; Sim, Chow‐Yen‐Desmond
Abstract: An aperture coupled microstrip‐line fed antenna (circular patch) with CP radiation is initially investigated. To achieve good CP radiation at 925 MHz UHF RFID frequency, the technique of loading an inverted C‐shaped slit into the circular patch is initially proposed. By further loading an open eccentric‐ring shaped parasitic element around the circular patch, an additional CP frequency can be excited at 910 MHz, and by combining these two CP frequencies, broad CP bandwidth that can cover the entire 902‐928 MHz UHF RFID band is achieved. Because of the parasitic element, the total dimension of proposed antenna is modified to 170 × 170 × 11.4 mm 3 . From the measured results, the impedance and CP bandwidths of the proposed antenna were 9.4% (859‐944 MHz) and 3.1% (902‐930 MHz). Furthermore, its corresponding peak gain and efficiency are 5.9 dBic and 84.3%, respectively. Further analyses have shown that the proposed antenna can also achieve good CP frequency agility across the desired UHF RFID operating band (902‐928 MHz).